The Effect of Remittances on Economic Growth. A Comparative Analysis of Pakistan, Indonesia, and India - Jamshaid Ahmed; Erni Achmad; Yohanes Vyn Amzar (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2026)
This study examines the impact of  workers Remittances on economic growth in three developing countries Pakistan, Indonesia, India during the period 2010-2024 using panels data analysis. Remittances have become an important source of external finance for a lot of developing economies, and they often are expected to contribute to income growth and development. The objective of this research is to find out whether remittances have a significant impact on economic growth in selected countries. The research is based on secondary data gathered from the World Bank. Economic growth is the Gross Domestic Product (GDP), while the independent variable is the remittances by workers. Gross capital formation and inflation are added as control variables to account for investment and macroeconomic stability. The analysis considers Pooled Ordinary Least Squares and Random Effects panel models and the Hausman test is applied to determine the most appropriate estimation method. The results show that the Random Effects model is the most appropriate specification. The results indicate that there is a positive  impact of remittances on economic growth. In contrast, gross capital formation has a positive and significant impact while inflation has a negative effect on economic growth. These results suggest that while remittances provide a contribution to the national income, the contribution of remittances to economic growth is insignificant for the selected countries. The study emphasizes the role of productive investment and macroeconomic stability for sustainable growth and recommends that policymakers should promote the more productive use of remittances to support long-term economic development.